Deletion of ghrelin prevents aging‐associated obesity and muscle dysfunction without affecting longevity. Issue 4 (6th June 2017) - Guillory, Bobby; Chen, Ji‐an; Patel, Shivam; Luo, Jiaohua; Splenser, Andres; Mody, Avni; Ding, Michael; Baghaie, Shiva; Anderson, Barbara; Iankova, Blaga; Halder, Tripti; Hernandez, Yamileth; et al.
Summary: During aging, decreases in energy expenditure and locomotor activity lead to body weight and fat gain. Aging is also associated with decreases in muscle strength and endurance leading to functional decline. Here, we show that lifelong deletion of ghrelin prevents development of obesity associated with aging by modulating food intake and energy expenditure. Ghrelin deletion also attenuated the decrease in phosphorylated adenosine monophosphate‐activated protein kinase (pAMPK) and downstream mediators in muscle, and increased the number of type IIa (fatigue resistant, oxidative) muscle fibers, preventing the decline in muscle strength and endurance seen with aging. Longevity was not affected by ghrelin deletion. Treatment of old mice with pharmacologic doses of ghrelin increased food intake, body weight, and muscle strength in both ghrelin wild‐type and knockout mice. These findings highlight the relevance of ghrelin during aging and identify a novel AMPK‐dependent mechanism for ghrelin action in muscle.